PENGEMBANGAN VIDEO ANIMASI INFORMASI KARIR UNTUK PERENCANAAN KARIR DI SEKOLAH MENENGAH PERTAMA - Muharandri, Citra; Astuti, Indri; Putri, Amallia (Universitas Tanjungpura, 2024)
Developing animated videos is the aim of this research. The ADDIE development model is used in conjunction with Research and Development (RD) methods. There are several stages of research using the ADDIE development model: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Six expert validation participants and 69 class IX students of SMP Negeri 18 Pontianak participated in this research. Data collection includes questionnaires and indirect interviews. Data from questionnaires are tested using descriptive analysis. The animated video material was validated by two material experts (average score of 3.5), two media experts (average score of 4.06), and two design experts (average score of 4.5) in the